Compact V-Shaped MIMO Antenna For LTE And 5G Applications - Mohammed Ibrahim, Ayman; Mohd Ibrahim, Imran; Shairi, Noor Azwan (Wydawnictwo SIGMA-NOT, 2020)
A compact sierpinski MIMO antenna was designed in the bands of 4.4 - 4.9 GHz and 5.15 - 5.925 GHz.The proposed dimension of the antenna were 21 × 24 × 0.8 mm, and was fabricated with inexpensive FR4 substrate with a thickness of 0.8 mm, a dielectric constant of 4.3, and 0.035-mm thick copper lining. The fabrication and measurement outcomes derived from the MIMO prototypes revealed that the proposed MIMO antennas are better in terms of size, isolation and the ECC. These attributes are suitable for LTE and 5G smartphone applications, which are being introduced into Chinese and Japanese markets.